Clinicopathological Study of Mucormycosis in Post Covid Patients, an Epidemic in Pandemic - Divya Pujari Jayakeerthy; Pradeep Kumar Reddy Mereddy; Adicherla Govardhan; Seema Bijjaragi (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2022)
Mucormycosis is an angio-invasive disease caused by saprophytic fungi of the order Mucorales. Mucormycosis has been established and recognized as a complication of the SARS-CoV-2 infection. Mucormycosis, well known as